Subduction of the Bangong–Nujiang Ocean: constraints from granites in the Bangong Co area, Tibet. (4th June 2013) - Liu, Deliang; Huang, Qishuai; Fan, Shuaiquan; Zhang, Liyun; Shi, Rendeng; Ding, Lin
<x xml:space="preserve">Abstract</x> We report geochronologic, whole‐rock geochemical and Sr–Nd isotopic analyses of the granites that are exposed to both the north and the inside of the Bangong–Nujiang Suture (BNS) zone as well as the implications for the Mesozoic history of Tibet. To the north of the BNS, the Larelaxin pluton consists of I‐type quartz diorite and highly fractionated I‐type biotite granite. The Larelaxin pluton is enriched in large‐ion lithophile elements (LILE) but depleted in high‐field‐strength elements (HFSE); therefore, it exhibits the features of volcanic arc rocks. The initial Sr (0.7102 to 0.7215) and negative εNd (t) (−2.91 to −5.20) values imply a mixture of depleted mantle and continental crust. The mean 206Pb/238U zircon age is 168 Ma; we therefore propose that the Bangong–Nujiang Ocean (BNO) had already been subducted beneath the Qiangtang terrain by the middle Jurassic. Inside the BNS, the Rutog granites intruded into the Lagongtang and Duoren formations, which show a continental margin and a forearc basin sedimentary facies, respectively. The mean 206Pb/238U zircon age is 101 Ma. The Rutog granites are monzogranites with a high Na/K ratio (Na2O/K2O > 1) and a high LILE/HFSE ratio, and A/CNK < 1.1. The high Sr/Y ratio (22 to 56) implies that these granites are adakitic. The low initial Sr (0.7044 to 0.7055) and positive εNd (t) (+1.46 to +2.70) values indicate that the protolith of the Rutog granites originated mainly from a depleted source. We attribute the Rutog plutonism to the development of an oceanic arc during the continuing northward subduction of the BNO and propose that the Rutog adakitic granites were formed by melting of the subducted BNO crust with limited crustal contamination. Copyright © 2013 John Wiley & Sons, Ltd.